Age, gender, and score distributions of moral foundations - Michael Zakharin; Timothy C. Bates (PLoS ONE, 2026)
Claims of generational differences in moral values have important implications for understanding societal change. Using the recently developed Moral Foundations Questionnaire (MFQ-2), we examined age and gender effects on moral foundations in large US (N = 835) and UK (N = 1,659) samples. Across both nations, binding foundations (proportionality, loyalty, authority and purity) showed consistent age-related increases. While these yearly increments were modest, they accumulated to substantial differences between youngest and oldest participants, with binding scores approximately 0.75 standard deviations higher in older adults. Among individualizing foundations, the preference for equality decreased with age, while harm/care remained stable. Gender differences emerged systematically: women scored higher on individualizing foundations, while men showed elevated scores on binding foundations. We also observed significant distributional effects, with care scores clustering near the scale maximum and purity scores near the minimum. These demographic patterns suggest important dynamics in how moral values may shift across generations and between genders, with implications for understanding social change.